Digital Transformation of the Notary Profession: Juridical Analysis of Cyber Notary Implementation in Authentic Deed Making in Indonesia - Alex Ramalus; Fauzi Syam; Dwi Suryahartati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Digital transformation in the field of notary is a structural imperative in the era of rapid development of information technology. The concept of Cyber Notary is present as a form of modernization of the notary position through the integration of technology such as electronic signatures, video conferencing, and digital document management and storage systems. This study aims to examine the juridical aspects of the implementation of Cyber Notary in the making of authentic deeds in Indonesia. The method used is a normative legal research method with legislative, conceptual, and comparative approaches. The results of the study show that there is no explicit regulation in the Law on Notary Positions (Law No. 30 of 2004 jo. Law No. 2 of 2014) related to the practice of Cyber Notary causing legal uncertainty, especially in terms of the validity of digital deeds and verification of the identity of the parties. In addition, the lack of suboptimal digital infrastructure and information security systems increases the risk of ethical violations and data leaks. The conclusion of this study emphasizes the importance of regulatory reformulation through the harmonization of the UUJN with the ITE Law and the PDP Law, as well as the need for digital competency development and the renewal of the notary profession code of ethics so that the implementation of Cyber Notary can be carried out legally, accountably, and professionally.